Comparative study between cases of previous one cesarean section delivered at Kafr El-Sheikh hospitals, versus those delivered at Tanta Uniersity Hospital - Mostafa, Asmaa A.; El-Khiat, Ahmed M.; El-Gergawey, Adel E.; Ismail, Mohammed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Many factors have contributed to the increasing rates of CSs, including increases in maternal age, BMI, and changes in obstetric practices and technologies. CSs requested by the mother and fear of litigation among caregivers have now become one of the most common indications of CS. Aim of this study was to compare between conditions of previous one caesarean section subjects delivered at Kafr El-Sheikh general hospitals, versus those delivered at Tanta University hospital as regard integrity of the uterine scars, presence of adhesions, time of termination, and fetal outcomes. Methods: This study was an observational study that was carried out on 100 pregnant ladies with history of previous one caesarean section. Participants were divided into two groups: group I included 50 pregnant women selected from Tanta University hospitals, group II included 50 pregnant women selected from Kafr El-Sheikh General hospital. Results: The estimated blood loss was significantly higher in cases selected from Kafr El-Sheikh hospitals compared to that lost from cases selected from Tanta University hospitals. Furthermore, operation time was significantly longer in patients selected from Kafr El-Sheikh hospitals than those selected from Tanta University hospitals. Additionally, omental adhesion was observed in 5 cases (5%); 3 (6%) from those selected from Kafr El-sheikh hospitals and 2 (4%) from those selected from Tanta University hospitals. As regard post-operative blood transfusion, there were increase in the incidence of post-operative blood transfusion in pregnant women selected from Kafr El-Sheikh hospitals (8%) compared to those selected from Tanta University hospitals (4%), but without statistically significant difference (p=0.678). Conclusions: There is high rate of caesarean section in our country. But satisfactory results were present in both Tanta university hospitals and Kafr El-Sheikh general hospital with few complication rates found special in cases priory delivered at Tanta University hospitals including less adhesion finding and thus less intra and post-operative complications.